The implementation of a collaborative peer interactive mathematics classroom learning environment - Ireland, Dennis V. (Curtin University, 2000)
In this study, the students in my Year 8 high school mathematics class and I set out to develop a functional and effective collaborative peer interactive classroom learning environment. This research was informed by the multiple theoretical perspectives of collaborative learning in mathematics education, Vygotskian learning and teaching approaches, and the Constructivist referent for pedagogic practices. Merging these perspectives into a viable foundation for our classroom practices led to the successful development of our collaborative peer interactive classroom learning environment.Working in groups of three or four, the students developed their social norms and utilised a collaborative approach to their learning of mathematics. Groups engaged in discussion, explanation, negotiation, peer teaching, giving help, receiving help and consensus building as part of their daily routine in our classroom. I kept qualitative and quantitative records of our progress as we worked to improve our collaborative peer interactive classroom learning environment during the first six months of the school year. I collected daily fieldnotes, audio and video recordings, observations taken by researcher colleagues, learning environment surveys and a variety of other artefacts. All of this data was analysed daily, weekly and monthly, so producing the monthly narratives upon which we based our determination of the success of this implementation.By adopting a Vygotskian perspective we utilised our peer interactive environment to develop and enhance 'scientific' and 'everyday' concepts through individual and group dynamic, overlapping (multiple) 'zones of proximal development' as well as our classwide 'zone of proximal development'. Our constructivist perspective aided us in focusing on our prior knowledge and experiences, which in turn enhanced the effectiveness of our collaborative classroom learning environment. We utilised the MCI and CLES learning environment measures to direct our endeavours to further improve our collaborative peer interactive classroom learning environment. The detailed analysis of the data from Months 1, 2 and 3 of this implementation, coupled with highlight analysis of the data from Months 4, 5 and 6, led me to conclude that teachers and their students can develop a functional and effective collaborative peer interactive classroom learning environment based on the multiple theoretical perspectives utilised in this study.This research improved my practice as a teacher and provided a functional and effective collaborative peer interactive classroom learning environment for the students to work in. It informed many of the calls for further research of this type and established that the theoretical concepts, upon which the implementation was founded, were valuable and useful in the practical setting of our collaborative peer interactive classroom. The findings are also valuable for the support which they offer to the latest movements in education, particularly the student-centred, outcomes-based approaches to learning and teaching. These approaches advocate the use of collaborative learning environments, and this study provides strong guidance as to how such environments can be successfully implemented.